Das mudanças nas práticas e processos fotográficos em função dos dispositivos tecnológicos: uma análise da flânerie ao longo de três séculos - Frandoloso, Luis Fernando (2015)
This thesis proposes a walk through the streets in the company of photographers who used this environment as source of inspiration for image registration. As a technical principle many processes and image production practices, the picture occupies an important place inside the media. From this point, the general aim of this work is to investigate, through different theoretical approaches and their joints such as technological changes in photographic devices involve the reconfiguration of practices and processes for capturing images from the urban landscape. To enrich the discussion about the use of photographic devices in this context, research relies on the flâneur figure, through this curious and fascinating character quoted in the work of the French poet Charles Baudelaire and the German Walter Benjamin studies, analyze how the landscape of cities and streets interfere in the conduct of photographer, involving different ways of moving and therefore look to urban landscape in order to register it. From the understanding of the evolution of the devices and the different ways to walk the cities, relating the flâneur with street photographer, this text unfolds into possible connections and experiences that such relationships raise. To conduct the study was determined as trimming, the choice of images from four names that have their photographic work performed mainly on the streets, and incorporating in his work a recurring element in capturing your images in this urban space: the chance. Therefore, this research part of the decisive moment of conception, understood as the unique in photo taking time credited to Henri Cartier-Bresson, one of four names chosen in this work, which relates to the chance present in his work (admitted even by the same). Throughout each chapter records were addressed chance in the work of three other selected photographers, namely: Bruce Gilden, Vivian Maier and the brazilian Pedro Garcia, who uses the alias, curiously, of Cartiê -Bressão. Reading and the analysis of selected images as well as the interview with Pedro Garcia, possible to identify continuities and ruptures in the photographic act to catch coincidences generated by different types of devices as well as new possibility of seein images. The evolution of devices also imply changes in the act of walking and to scroll through the spaces, pointing to the emergence of a possible new flâneur that the from the second decade of this century, capturing his photographic chances with cameras coupled to cell phones (addressed in this dissertation as mobile devices), passes now share them on social networks, especially in Instagram.